Concept of Punishment - Yolanda Hendartin; Muhammad Faiz Al Maisi; Ananda Tama Rizky; Meldyana Permata Abdillah (ISNU Sumatera Utara, 2025)
Sentencing is an important part of criminal law. This is because sentencing is the culmination of the entire process of holding someone guilty of committing a crime accountable.